Determinants and Impact of Online Reviews on Product Satisfaction. Issue 1 (2nd January 2020) - Changchit, Chuleeporn; Klaus, Tim
Abstract: As an increasing number of consumers prefer online shopping, online customer reviews play an important role in a customer's pre-purchase decisions. Both reviews and product information are seen as a guide that impacts a customer's decision process. Given the growing importance of E-commerce, this study examines the impact that online reviews and product details have on customers' product satisfaction. In this study, we specifically explore the role that a customer's product certainty and review helpfulness have on product satisfaction. The study furthers the body of knowledge regarding online reviews and factors that influence customers' product satisfaction. The study results provide insight into the factors that should help E-commerce companies adapt their business model to better fit consumers' expectations.